Anthropological and Forensic Aspects of Odontological Variation in Two Contemporary Australian Populations - Alison S. Chiu; Denise Donlon (Dental Anthropology Association, 2000)
The utilization of odontometric variation as a discriminator between modern human groups continues to decline, despite its value in both anthropological and forensic contexts. Traditional odontometric methods, coupled with advanced statistical methods, are applied to illustrate the continuing usefulness of these techniques. The ability to discriminate between the major population groups (Caucasoid and Mongoloid) in the Sydney region of Australia, based on dental dimensions, is extremely valuable in the forensic identification of individuals. Furthermore, metric variation in the dentition of these contemporary populations is poorly understood in this region of the world. The utility of variation in tooth dimensions in discriminating between these two groups is explored. Dental stone casts of the permanent maxillary and mandibular dentition of 198 individuals were made, and mesiodistal and buccolingual crown diameters were recorded for each tooth. Both univariate and multivariate analyses were used to investigate differences in linear and areal dimensions, as well as the predictive value of these measures in a forensic context, using discriminant function analysis (DFA). DFA produced separation of Caucasoids and Mongoloids with a success rate of 93.9% on the basis of these measurements. Separation of the groups was most apparent in the mesiodistal and buccolingual dimensions of the maxillary first premolar (P1), the mesiodistal diameter of the maxillary second premolar (P2), and the mesiodistal dimension of the mandibular first premolar (P1). The results from this study further highlight the usefulness of dental metrics in forensic applications and contribute to our knowledge of the variation of these features in contemporary human populations.